Communication Strategy in Social Conflict Resolution of Residents Affected by the Indonesian Capital City - Sutanto, Margono Hadi; Djalil, Nur Alim; Sukmarini, Andi Vita (Journal La Sociale, 2023)
This research investigates communication strategies between the residents of Nusantara Capital City developmental areas and other groups as they continue grappling with social conflict after the relocation to East Kalimantan. This research was carried out at Security and Social, Cultural, and Community Development of Nusantara Capital City Authority, Deputy. Record data was undertaken through the following processes: face to face interviews with informants, observation and documentation to acquire the necessary data. This type of research employs qualitative research. This study findings establish the fact that most social issues affecting residents and leading to conflict can be dealt with by the strategies employed by the Nusantara Capital Authority through the Deputy Social, Cultural and Community Empowerment. The techniques employed in dealing with social conflict within residents that have been displaced by development of the Nusantara Capital City are are categorized under communication strategies currently classified as informative, persuasive, instructive and human relations communication. Of the strategies involved in the approach, persuasive communication strategies are predominant in managing social conflicts that occur among residents who are affected by the development of the Nusantara Capital City and can influence drastic changes in the behaviour of some of the affected residents who are against development of the Nusantara Capital City. Some of the key determinants for impact of communicable goals type of strategy are Credibility/ Trust; Clear Message and Media used for conveying information, social media as well as the electronic media.